SINTESIS DAN KARAKTERISASI NANO ZnO DOPING CU - Siltiwi Mandar; Rahadian Zainul (Departemen Kimia FMIPA UNP, 2019)
The photodegradation process is a combination of photochemical processes with catalysts which are generally semiconductor materials. One of the photocatalysts that is being developed is zinc oxide (ZnO) in nanometer size to optimize the degradation process of organic compounds. Synthesis Nano zinc oxide (ZnO) can use the sol-gel method, the sol-gel method is the best method in making nanoparticles that produce uniform size and high purity. XRD (X-Ray Diffraction) test results show the size of Nano zinc oxide (ZnO) which is 27 nm. Nano zinc oxide (ZnO) has a band band 3.37 eV so that it is less suitable to be applied to visible light. Therefore it is necessary to do coupling with other metals such as Cu. The results of Nano zinc oxide (ZnO) doped Cu 7% have a low band gap of 2.57 eV so that it is easy to excite valence band electrons to the conduction band.